2018
DOI: 10.15619/nzjp/46.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in exercise for people with Parkinson’s: What is meaningful?

Abstract: Whilst it is suggested that exercise is integral in the management of Parkinson’s, there is minimal literature exploring this population’s perceptions about exercise, and how these perceptions relate to standardised physical outcome measures. This mixed method study explored participants’ views on an exercise programme which was offered as part of an intervention in a randomised controlled trial for people with Parkinson’s. Participants in the intervention group (n = 21) received an exercise programme and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The thirteen included studies were published from 2004 to 2021, with one study from 2004 [20] and the remaining twelve studies from 2014 to 2021. There were four studies from the US, [21][22][23][24] two each from the UK, [25,26] Australia [27,28] and the Netherlands, [29,30] and one from each of Sweden, [20] New Zealand, [31] and Canada. [32] Most of the studies reported a specific purpose -e.g., how patients view the role of their GP, [29] or patients' perceptions of a specific exercise [22,27,31] or prevention program, [21] or of their perioperative experiences.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thirteen included studies were published from 2004 to 2021, with one study from 2004 [20] and the remaining twelve studies from 2014 to 2021. There were four studies from the US, [21][22][23][24] two each from the UK, [25,26] Australia [27,28] and the Netherlands, [29,30] and one from each of Sweden, [20] New Zealand, [31] and Canada. [32] Most of the studies reported a specific purpose -e.g., how patients view the role of their GP, [29] or patients' perceptions of a specific exercise [22,27,31] or prevention program, [21] or of their perioperative experiences.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were four studies from the US, [21][22][23][24] two each from the UK, [25,26] Australia [27,28] and the Netherlands, [29,30] and one from each of Sweden, [20] New Zealand, [31] and Canada. [32] Most of the studies reported a specific purpose -e.g., how patients view the role of their GP, [29] or patients' perceptions of a specific exercise [22,27,31] or prevention program, [21] or of their perioperative experiences. [23] All studies applied a qualitative design with interview data; one study supplemented this with video recordings [29] and one study applied a mixed-methods design.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the studies reported a speci c purpose -e.g., how patients view the role of their GP (26), or patients' perceptions of a speci c exercise (20,24,27) or prevention program (19), or of their perioperative experiences (21).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The ten included studies were published from 2004 to 2020, with one study from 2004 (18) and the remaining nine studies from 2014 to 2020. There were three studies from the US (19)(20)(21), two each from the UK (22,23) and Australia (24,25) and one from each of Sweden (18) the Netherlands (26) and New Zealand (27).…”
Section: Study Characteristicsmentioning
confidence: 99%